Sexual behavior of school-aged adolescents in the city of Goiânia, Goiás - Reinaldo Satoru Azevedo Sasaki; Márcia Maria de Souza; Cláudio Rodrigues Leles; Deborah Carvalho Malta; Luciana Monteiro Vasconcelos Sardinha; Maria do Carmo Matias Freire (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
OBJECTIVE: To investigate the characteristics of sexual behavior in school-aged adolescents and possible differences regarding sex and type of school. METHODS: Cross-sectional study using data from the National Adolescent School-based Health Survey (PeNSE) 2009, carried out by the Brazilian Ministry of Health, in partnership with the Brazilian Institute of Geography and Statistics (IBGE). The sample consisted of 3,099 9th graders living in Goiânia, State of Goiás, Brazil, mostly aged between 13 to 15 years old, who answered a self-applicable questionnaire on risk and protective health factors. The Rao-Scott test was used in the statistical analysis, considering the complex sample design. RESULTS: The prevalence of sexual intercourse was of 26.5% (95%CI 23.8 - 29.4) at least once in life and of 18.5% (95%CI 16.5 - 20.8) in the last year. Both behaviors were more frequent among male students and among those attending public schools. Most of the respondents had their first intercourse at the age of 13 or younger, with up to 3 partners. They had also used a pregnancy prevention method in the last intercourse, and received guidance on prevention at school. The age of the first intercourse was earlier and the number of partners was higher among male students. More females and those attending public schools reported having received information on pregnancy prevention. Guidance on STD/AIDS was also more frequent in public schools. CONCLUSION: Results showed a need for health education measures involving education and health professionals, as well as parents, to reduce the discrepancies found regarding sex and type of school.